Functionalized boron carbide for enhancement of anticorrosion performance of epoxy resin. (2nd October 2017) - Wang, Jizhuang; He, Yi; Xie, Zhengfeng; Chen, Chunlin; Yang, Qiangbin; Zhang, Chunli; Wang, Binyan; Zhan, Yingqing; Zhao, Tianhong
Abstract : In this study, epoxy coatings were modified by adding various compositions of B4 C particles. In order to achieve proper dispersion of particles in the epoxy coating and increasing chemical interactions between particles and polymeric coating, the surface of the B4 C particles was treated with γ‐(2, 3‐epoxypropoxy) propytrimethoxysilane (KH560). The surface modification and microstructure of B4 C were characterized by Fourier transform infrared, X‐ray diffraction, X‐ray photoelectron spectroscopy, scanning electron microscopy, and transmission electron microscopy. Electrochemical impedance spectroscopy was also used to evaluate the impedance of coatings. The results revealed that the KH560 not only enhanced the interaction between B4 C particles and epoxy resin but also exhibited a remarkable ability to improve the anticorrosion performance of epoxy resin. The epoxy coating with the 3 wt% B4 C‐KH560 particles exhibited the best anticorrosion performance, which can be attributed to the best uniform dispersion of the B4 C‐KH560 particles, and the particles effectively block the aggressive species (Cl −, O2, and H2 O) from the coating.